The Efficacy and Safety of Propiverine Hydrochloride in Patients with Overactive Bladder Symptoms Who Poorly Responded to Previous Anticholinergic Agents. (28th June 2011) - Masumori, Naoya; Miyamoto, Shintaro; Tsukamoto, Taiji; Furuya, Seiji; Iwasawa, Akihiko; Sato, Takashi; Itoh, Naoki; Shibuya, Akihiko; Oda, Toshiro
Abstract : Objectives . To prospectively examine the efficacy and safety of propiverine hydrochloride in patients with overactive bladder (OAB) symptoms who poorly responded to previous treatment with solifenacin, tolterodine or imidafenacin. Methods . Patients aged ≥20 with persisting OAB symptoms (≥6 in OAB symptom score (OABSS)) even after at least 4-week treatment using solifenacin, tolterodine or imidafenacin were enrolled. Propiverine 20 mg/day was administered for 12 weeks to 70 patients who desired the further improvement of OAB symptoms and 3 who had intolerable adverse events of previous drugs. The OABSS and postvoid residual urine volume (PVR) were determined before and at 4 and 12 weeks of treatment. Results . Of 73 patients enrolled (29 males and 44 females, median age 71 years), 52 completed the protocol treatment. The OABSS was significantly improved by propiverine treatment (9.0 at baseline, 6.2 at 4 weeks, 6.3 at 12 weeks (P < 0.001 )). The scores of OAB symptoms (nighttime frequency, urgency and urge incontinence) except daytime frequency also improved significantly. No increase in PVR was observed. The most frequent adverse event was dry mouth (13.7%), followed by constipation (6.8%). Conclusions . Propiverine is useful to improve OAB for patients who poorly respond to solifenacin, tolterodine or imidafenacin.